Application of Nanoemulsions (W/O) of Extract of Opuntia oligacantha C.F. Först and Orange Oil in Gelatine Films - Salvador Omar Espino-Manzano; Arely León-López; Gabriel Aguirre-Álvarez; Uriel González-Lemus; Laurette Prince; Rafael Germán Campos-Montiel (Molecules, 2020)
Over the past decade, consumers have demanded natural, completely biodegradable active packaging serving as food containers. Bioactive plant compounds can be added to biopolymer-based films to improve their functionality, as they not only act as barriers against oxidation, microbiological, and physical damage, they also offer functionality to the food they contain. A water-in-oil (W/O) nanoemulsion was produced by applying ultrasound to xoconostle extract and orange oil, and was incorporated into gelatine films in different proportions 1:0 (control), 1:0.10, 1:0.25, 1:0.50, 1:0.75, and 1:1 (gelatine:nanoemulsion). The nanoemulsions had an average size of 118.80 ± 5.50 nm with a Z-potential of −69.9 ± 9.93 mV. The presence of bioactive compounds such as phenols, flavonoids, and betalains in the films was evaluated. The 1:1 treatment showed the highest presence of bioactive compounds, 41.31 ± 3.71 mg of gallic acid equivalent per 100 g (GAE)/100g for phenols, 28.03 ± 3.25 mg of quercetin equivalent per 100 g (EQ)/100g flavonoids and 0.014 mg/g betalains. Radical inhibition reached 72.13% for 2,20-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS), and 82.23% for 1,1-diphenyl-2-picrylhydrazyl (DPPH). The color of the films was influenced by the incorporation of nanoemulsions, showing that it was significantly different (p < 0.05) to the control. Mechanical properties, such as tensile strength, Young’s modulus, and percentage elongation, were affected by the incorporation of nanoemulsified bioactive compounds into gelatine films. The obtained films presented changes in strength and flexibility. These characteristics could be favorable as packaging material.